Playing amongst the ruins. - Gleadowe, Teresa; Barratt, Paul; Hammonds, Chris; Horne, Rosalind (London : The Royal College of Art, 2001)
Acconci, Vito ; Bock, John ; Durant, Sam ; Gelatin ; Halley, Peter ; Henning, Anton ; Lambri, Luisa ; Morris, Sarah ; Müller, Matthias ; Rosler, Martha et al.
Playing amongst the ruins, The Royal College of Art Galleries, London, 2 March - 1 April 2001
kunstcatalogus